Investment behavior in the Egyptian stock market: The impact of social media on investor decision-making - Abdelrehim Awad; Adel Fathy Aziz; Talaat Rashad Shma (Investment Management & Financial Innovations)
Social media significantly influences investor behavior, particularly in emerging markets like the Egyptian stock market. This study examines its impact on trading frequency, herding behavior, and overconfidence among Egyptian investors. Data were collected through a structured survey of 300 active investors, distributed via two prominent Facebook pages: “The Popular Union of Investors in the Egyptian Stock Market” and “Investment in the Egyptian Stock Market.” The sample was determined using Cochran’s formula for large, undefined populations, achieving a 78% response rate from the 385 recommended respondents. A descriptive quantitative approach was employed, utilizing correlation tests and regression analysis to assess relationships between social media engagement and investor behavior.Findings indicate that social media usage significantly increases trading frequency, as investors make more reactive decisions based on rapidly available information. Herding behavior is also positively associated with social media engagement, demonstrating that investors tend to follow market trends and decisions discussed in online communities. Additionally, social media exposure fosters overconfidence, leading to increased risk-taking behavior. These insights highlight the critical role of social media in shaping investor behavior, with practical implications for regulators, financial advisors, and individual investors. Regulators should promote investor education on the cognitive biases linked to social media engagement, while financial advisors must address its influence on client decision-making. Future research should explore platform-specific features, such as visual content and influencer-driven financial advice, to better understand their effects on investment strategies. AcknowledgmentThe authors are thankful to the Deanship of Graduate Studies and Scientific Research at University of Bisha for supporting this work through the Fast-Track Research Support Program.